2013 Ninth International Conference on Natural Computation (ICNC) 2013
DOI: 10.1109/icnc.2013.6817966
|View full text |Cite
|
Sign up to set email alerts
|

Reliable modeling of chemical duarability of high level waste glass using bootstrap aggregated neural networks

Abstract: Modeling chemical durability of high level waste glass for nuclear waste processing using bootstrap aggregated neural networks is studied in this paper. In order to overcome the difficulty in developing detailed mechanistic models, data driven neural network models are developed from experimental data. A key issue in building neural network models is that model generalization capability cannot be guaranteed due to the potential over-fitting problem and the limitation in the training data. In order to enhance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Bootstrap aggregated neural network was proposed by Zhang [19]. It is shown that this type of aggregated models can achieve great performance in many applications with improved robustness [20][21][22][23][24]. Based on the idea of stacking several networks to enhance model performance, many approaches were proposed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Bootstrap aggregated neural network was proposed by Zhang [19]. It is shown that this type of aggregated models can achieve great performance in many applications with improved robustness [20][21][22][23][24]. Based on the idea of stacking several networks to enhance model performance, many approaches were proposed in recent years.…”
Section: Introductionmentioning
confidence: 99%